2020
DOI: 10.25122/jml-2019-0071
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination after Cardiac Surgery in a Hospital Cardiac Surgery Ward

Abstract: Surgery site infection is one of the most common postoperative complications which is associated with increased morbidity, mortality and admission costs. It is considered a priority to determine the level of nosocomial infection and its control in reflecting the quality of care. Therefore, this study aimed to evaluate the microbial contamination after cardiac surgery at a hospital cardiac surgery ward of Besat Hospital, Tehran. In this cross-sectional descriptive-analytic study (2013-2017), 610 patients underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…It is difficult to estimate the incidence of infection in cardiac surgery patients, with reported rates ranging between 3.5% and 26.8% [ 10 , 15 , 16 , 17 , 18 ]. SSI incidence after cardiac surgery varies depending on the quality of local epidemiological surveillance, SSI definition used, patient profile and the type of cardiac procedure [ 19 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…It is difficult to estimate the incidence of infection in cardiac surgery patients, with reported rates ranging between 3.5% and 26.8% [ 10 , 15 , 16 , 17 , 18 ]. SSI incidence after cardiac surgery varies depending on the quality of local epidemiological surveillance, SSI definition used, patient profile and the type of cardiac procedure [ 19 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The most common complications of cardiac surgeries are infections. An international study investigating microbial infections after cardiac surgery in cardiac surgery wards, conducted with 123 patients, found that 17-23% of patients develop SSIs after cardiac surgical procedures, as these patients have higher risk factors and vulnerabilities (4) .…”
Section: Introductionmentioning
confidence: 99%
“…A complicação mais recorrente das cirurgias cardíacas são as infecções. Um estudo internacional com o objetivo de investigar infecções microbianas após cirurgia cardíaca em enfermarias de cirurgia cardíaca, desenvolvido com 123 pacientes, verificou que de 17% a 23% dos pacientes apresentam ISCs após procedimento cirúrgico cardíaco, uma vez que esses pacientes possuem maiores fatores de risco e debilidade (4) .…”
Section: Introductionunclassified